2015
DOI: 10.1111/jch.12700
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Ambulatory Blood Pressure in the Obese: The Ambulatory Blood Pressure‐International Study

Abstract: The purpose of this study was to compare the predictive value of ambulatory blood pressure (BP) vs office BP for cardiovascular events during a 5.8-year follow-up period in the obese and nonobese participants of the Ambulatory Blood Pressure-International Study (n=10,817). Both ambulatory BP and office BP considered separately were predictive of cardiovascular events. However, in Cox models including both pressures, only ambulatory BP was associated with outcome. Among obese patients, the hazard ratios for a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Ambulatory 24-hour BP measurement is more reliable than single or multiple office measurements to identify hypertension and as a predictor of cardiovascular outcomes. 52,53 It is currently the diagnostic tool recommended to confirm a diagnosis of hypertension. The Longitudinal Victorian Infant Collaborative Study of EPT and/or extremely low birth weight (ELBW) survivors performed a single reading of office BP at 8 years and revealed no differences compared with term control group members.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory 24-hour BP measurement is more reliable than single or multiple office measurements to identify hypertension and as a predictor of cardiovascular outcomes. 52,53 It is currently the diagnostic tool recommended to confirm a diagnosis of hypertension. The Longitudinal Victorian Infant Collaborative Study of EPT and/or extremely low birth weight (ELBW) survivors performed a single reading of office BP at 8 years and revealed no differences compared with term control group members.…”
Section: Discussionmentioning
confidence: 99%
“…At present, no antihypertensive intervention would be approved without having been assessed by out‐of‐office BP measurements (Mancia et al., ), mostly due to the greater prognostic value of ambulatory BP measurements in comparison with office BP (Palatini et al., ). That should be the same for non‐pharmacological measures such as physical activity.…”
mentioning
confidence: 99%
“…The authors conclude that their results indicate that ABPM is as accurate in obese patients as in nonobese patients, at least insofar as the prediction of CVEs is concerned, and that ABPM may be offered as readily to obese patients as to those who are not obese. 1 This finding has important implications for practice. Firstly, the study does not show that ABPM is as accurate in obese as in nonobese patients.…”
mentioning
confidence: 94%
“…Moreover, the study showed that the good prognostic performance of ABPM was also maintained in the group of patients with more severe obesity. The authors conclude that their results indicate that ABPM is as accurate in obese patients as in nonobese patients, at least insofar as the prediction of CVEs is concerned, and that ABPM may be offered as readily to obese patients as to those who are not obese …”
mentioning
confidence: 94%
See 1 more Smart Citation